Particle Size and Particle Size Distribution of Emulsion Polymers: A Review of Modeling Studies - Sood, Ashwini; Gaur, Tulika (Journal of Chemical Engineering Research Updates, 2020)
The aim of this work is to provide a literature review in the area of modeling of particle size and particle size distribution of emulsion polymers. Modeling studies of emulsion polymerization are of great interest due to the industrial importance of latexes produced. There are two broad strategies adopted to model particle size distribution: 1) Lumped model in which average particle size assuming the monodispersed distribution is modelled. 2) Distributed model or population balance model in which full particle size distribution is modelled. Lumped model serves as a learning model and a stepping stone to develop a population balance model.